Fungal Contamination of Restaurant Cold Foods in Kirkuk, Iraq: Bena (Β-Tubulin)–Based Mold Identification and PLB1 Screening in Candida Isolates - Hasan, Imad K.; Mohammed, Sanaa H. (American Journal of Biology and Natural Sciences, 2026)
Background: Fungal spoilage of restaurant foods, especially ready-to-eat and minimally processed products, is a pervasive issue due to the ability of yeasts and molds to withstand preparation and holding steps as well as impact upon shelf life with potential for consequences to hygiene control. RTE matrix like salads are highly susceptible to carry over and post-processing contaminations and surveys have been reported to have elevated yeast–mold counts beyond the permissible limits. Airborne dissemination in busy food-service settings may also play a role in the contamination of surfaces and exposed foods, therefore confirming the requirement for species-level identification. Thus, we examine the occurrence of mycological contamination in foods from restaurants employing conventional (culture-based) methods and validate mold identification with BenA (β-tubulin) sequences while assessing yeast isolates for virulence-associated PLB1 gene to contribute with a risk-aware interpretation. Materials and Methods: A total of 93 sinonasal swabs were taken from restaurant workers in Kirkuk, Iraq during the period from August to September 2025. Fungal strains were identified by culture morphology from SDA and CHROMagar Candida and then observed under a microscope. Phenotypic phospholipase activity was determined on egg yolk agar and molecular identification by PCR targeting β-tubulin and PLB1 genes. Results: Fungal growth was detected in 79.17% of samples, with Candida species predominating, particularly Candida krusei. Phenotypic phospholipase activity was absent among the yeast isolates. Molecular analysis confirmed accurate species-level identification of molds and revealed that 81.58%% of Candida isolates carried the PLB1 gene. Conclusions: restaurant cold foods exhibited significant yeast-dominated fungal contamination (Candida krusei in particular) and occasional molecularly proven molds - chances are for enzymes that save toxins but all assay negative.Further-more, the PLB1 carriage despite 100% phenotypic phospholipase negativity supports colonization-driven condition-dependent virulence expression which due to resistant biofilms may require tighter hygiene controls.